Health Insurance Literacy Levels of Information Intermediaries: How Prepared Are They to Address the Growing Health Insurance Access Needs of Consumers? - Jean Edward; Robin A. Thompson; Amanda Wiggins (SLACK Incorporated, 2022)
Background: With rising unemployment rates brought on by coronavirus disease 2019 pandemic, the rates of underinsured and uninsured consumers are likely to rise. Health information intermediaries play a critical role in assisting consumers with navigating the complexities of the United States health care system and the ever-changing health care policy landscape. Not much is known about the health insurance literacy (HIL) levels of information intermediaries and their ability to assist consumers with making informed decisions about their health insurance. Objective: This study aimed to examine the association between information intermediary levels of HIL, sociodemographic factors, and confidence and behaviors in assisting consumers with health insurance needs. Methods: We surveyed 118 information intermediaries from various roles to assess objective and subjective HIL, frequency, and confidence in assisting consumers, and confidence in understanding changes in federal health reform policies and state Medicaid waiver programs. Key Results: Less than one-half (39%) of information intermediaries had high subjective HIL and much fewer (13%) had high objective HIL. The average frequency of assisting consumers with health insurance scores were somewhat low, and confidence in assisting consumers with health insurance scores and confidence with understanding state and federal policies were modest. Results from our logistic regression model indicated that confidence in assisting consumers was found to be the only significant contributor to high subjective HIL. For every one-point increase on the confidence assisting subscale, there was a 35% increase in the information intermediaries having high subjective HIL. Conclusions: Findings from this study, coupled with rising uninsured rates, indicate the need for tailored training programs and resources to equip our information intermediaries to provide timely and appropriate health insurance support for consumers. [HLRP: Health Literacy Research and Practice. 2022;6(1):e30-e36.] Plain Language Summary: In a sample of 118 information intermediaries, representing community health workers, navigators, and other people in outreach roles, the majority had low subjective and objective HIL. We also found that as confidence with assisting consumers with health insurance needs increases, HIL increased as well. These findings indicate that tailored training programs and resources are needed to equip information intermediaries to provide health insurance support for consumers.